Symbolic Representation of War in Grave of the Fireflies (1988) - Jessica Angelina; Setefanus Suprajitno (Institute of Research and Community Outreach - Petra Christian University, 2025)
The evolution of animation has been closely tied to pop culture, particularly Japanese anime which significantly influences global animation. With over 430 anime production studios in Japan, Studio Ghibli has emerged as one of the most popular anime studios. Its popularity is partly due to its exploration of themes related to humanity and environmental issues, including war. Reflecting on the fact of how the film has served as a medium to criticize the war, Studio Ghibli confidently implied it in some of its films, one of which is Grave of the Fireflies (1988). This thesis goes beyond recent studies that focus solely on fireflies as symbols of wartime conditions. The broader symbolism used in Grave of the Fireflies will be analyzed to see the impact of war in physical and mental aspects before and after the war. By applying symbolism in war film theory to analyze physical and mental aspects, it shows the characters’ struggles, fears, aspirations, and sacrifices through symbols that appear throughout the film. Moreover, the findings indicate that all of the symbols used in this film have evolved into two opposing conditions: hopefulness and hopelessness.